2022
DOI: 10.7759/cureus.26162
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis Between Ketamine Versus Combination of Midazolam and Haloperidol for Rapid Safe Control of Agitated Patients in Emergency Department: A Systematic Review

Abstract: We aim to discuss the efficacy and adverse effects of using ketamine in agitated patients in the emergency department (ED) compared with the combination therapy of haloperidol with benzodiazepine. This systematic review followed Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) guidelines. An electronic search from PubMed/Medline, Cochrane library, and Google Scholar was conducted from their inception to 30 th April 2022. We included agitated patients in ED who were given infusion with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Additionally, a recent randomized trial showed that even though the risk of vomiting was high with ketamine/midazolam, it was significantly associated with a shorter duration for the induction of sedation and offered a less painful procedure than the midazolam/fentanyl combination [ 37 ]. Our previous systematic review also deduced that ketamine is more efficient in providing sedation than a combination of ketamine and haloperidol; however, it was associated with a significant risk for hypertension and tachycardia; thus, it should be used while taking into consideration the complications [ 38 ]. Moreover, we have previously shown opioids alone may offer better analgesia for patients with hip fractures; however, it is far less superior to ultrasound-guided regional analgesia [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…Additionally, a recent randomized trial showed that even though the risk of vomiting was high with ketamine/midazolam, it was significantly associated with a shorter duration for the induction of sedation and offered a less painful procedure than the midazolam/fentanyl combination [ 37 ]. Our previous systematic review also deduced that ketamine is more efficient in providing sedation than a combination of ketamine and haloperidol; however, it was associated with a significant risk for hypertension and tachycardia; thus, it should be used while taking into consideration the complications [ 38 ]. Moreover, we have previously shown opioids alone may offer better analgesia for patients with hip fractures; however, it is far less superior to ultrasound-guided regional analgesia [ 39 ].…”
Section: Reviewmentioning
confidence: 99%
“…Unfortunately, propofol use has some detrimental implications on the patients in some cases, such as hemodynamic compromise and respiratory depression; most of these effects depend on the dosage quantities. Additionally, according to a previous study, ketamine use is more effective when its main emphasis is to sedate the individual as fast as possible; however, it has some negative implications that must be considered [ 3 ]. Fortunately, despite the fact that the drug has been proven to have antiemetic and amnesiac effects, it is not analgesic [ 4 ].…”
Section: Introductionmentioning
confidence: 99%